Effects of Radiofrequency Electromagnetic Fields Emitted from Mobile Phones and Wi-Fi Router on the Growth Rate and Susceptibility of Enterococcus faecalis to Antibiotics - Seyed Mohammad Javad Mortazavi; Mohammad Taheri; Maryam Paknahad; Salar Khandadash (Journal of Biomedical Physics and Engineering, 2022)
Background: During the last decade, people have been dramatically exposed to radiation emitted from widely-used radiofrequency electromagnetic fields (RF-EMF) generating devices. Objective: This study aimed to evaluate the effects of exposure to RF-EMF emitted from smart phones and Wi-Fi routers on the growth rate and antibiotic sensitivity of Enterococcus faecalis (E. faecalis) as a pathogen in the root canals of teeth.Material and Methods: In this experimental study, E. faecalis ATCC 19115 was used, characterized and confirmed by morphological and biochemical tests. Antibiotic susceptibility test was measured for several common antibiotics. To perform antibiotic susceptibility tests, disk diffusion (Kirby-Bauer) method on Mueller-Hinton agar plates was used before and after exposure to RF-EMFs emitted from a commercial Wi-Fi router or a mobile phone simulator. Moreover, we measured the optical density at 625 nm after different exposure times using a calibrated UV-visible spectrophotometer to evaluate the effect of RF-EMF exposure on the bacterial growth rate. Results: Exposure to RF-EMF significantly altered the antimicrobial sensitivity of the E. faecalis. While, the susceptibility of the bacteria decreased significantly after 6 h of exposure, longer exposure time (e.g. exposure for 24 h) increased the susceptibility of the bacteria to all antibiotics. Furthermore, it was found that the bacteria tended to regress to their early state. Moreover, the non-exposed E. faecalis showed a slower growth rate than the bacteria exposed to RF-EMFs.  Conclusion: Exposure to RF-EMF emitted by Wi-Fi routers or mobile phone simulator can significantly change the antibiotic susceptibility and growth rate of E. faecalis.